Liver transplantation for the treatment of homozygous familial hypercholesterolaemia in an era of emerging lipid‐lowering therapies. Issue 6 (June 2014) - Page, M. M.; Ekinci, E. I.; Jones, R. M.; Angus, P. W.; Gow, P. J.; O'Brien, R. C.
Abstract Homozygous familial hypercholesterolaemia (FH) causes severe premature coronary artery disease because of very high levels of low density lipoprotein (LDL)‐cholesterol. Standard lipid‐lowering drugs and LDL‐apheresis may not be sufficiently effective. Liver transplantation replaces defective LDL receptors and vastly improves the lipid profile, and we present the first report of an Australian adult to receive this treatment. Emerging drug treatments for FH may be alternatives to LDL‐apheresis and transplantation, but long‐term safety and efficacy data are lacking for all of these options.